2019
DOI: 10.1111/echo.14480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of echocardiography for the diagnosis of native valve infective endocarditis in Staphylococcus aureus bacteremia

Abstract: Background The incidence of Staphylococcus aureus infective endocarditis (IE) is steadily rising due to advances in health care delivery. Routine echocardiography is essential in the management of Staphylococcus aureus bacteremia (SAB). The aim of this retrospective cohort study was to characterize the real‐world use of echocardiography in adult patients with SAB and native valve S aureus IE. Methods Using an academic hospital microbiological database, all cases of SAB in adults between 2010 and 2016 were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Secondly, our predefined cut-off points are not prospectively validated. Nevertheless, both the IE risk percentages selected and the use of NLR have previously been proposed and accepted by several authors (8,24,26,27,32). Thirdly, we cannot exclude that the higher 30-day mortality found in patients with no echocardiogram is caused to uncontrolled confounding variables.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Secondly, our predefined cut-off points are not prospectively validated. Nevertheless, both the IE risk percentages selected and the use of NLR have previously been proposed and accepted by several authors (8,24,26,27,32). Thirdly, we cannot exclude that the higher 30-day mortality found in patients with no echocardiogram is caused to uncontrolled confounding variables.…”
Section: Discussionmentioning
confidence: 94%
“…A potential restriction when applying these scores is that both their development and validation studies have been performed in cohorts without universal echocardiographic assessment, and only a small proportion of patients have undergone TEE. Several authors have demonstrated that carrying out an echocardiogram in a larger proportion of patients implies a higher rate of IE diagnoses (20,21,31,32). It has even been proposed that performing an echocardiogram in these patients may be associated with lower mortality (33).…”
Section: Discussionmentioning
confidence: 99%
“…A potential restriction when applying these scores is that both their development and validation studies have been performed in cohorts without universal echocardiographic assessment, and only a small proportion of patients have undergone TEE. Several authors have demonstrated that carrying out an echocardiogram in a larger proportion of patients implies a higher rate of IE diagnoses [ 24 , 25 , 26 , 36 , 37 ]. It has even been proposed that performing an echocardiogram in these patients may be associated with lower mortality [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, our predefined cutoff points are not prospectively validated and are based on scarce evidence. Nevertheless, both the IE risk percentages selected and the use of NLR have previously been proposed and accepted by several authors [ 12 , 17 , 21 , 29 , 32 , 37 ]. Third, we cannot exclude that the higher 30-day mortality found in patients with no echocardiogram is caused to uncontrolled confounding variables.…”
Section: Discussionmentioning
confidence: 99%